Superfluidity in the stochastic limit - L. Accardi; S. V. Kozyrev (Discrete Dynamics in Nature and Society)
We discuss the stochastic limit approach to superfluidity. Starting from the usual Hamiltonian describing the interaction between the Bose condensate and the normal phase, we prove the existence of superfluidity in the stochastic limit and deduce a nonlinear (quadratic) kinetic equation describing the evolution of the density of superfluid liquid.